Peningkatan Pengetahuan “Penyakit Kanker Prostat” pada Masyarakat Dusun Mapung Buttu Kecamatan Campalagian, Kabupaten Polewali Mandar: Increasing Knowledge of "Prostate Cancer" in the Mapung Buttu Hamlet Community, Campalagian District, Polewali Mandar Regency - Hafsah Hafsah; Hasria Alang; Muh. Sri Yusal (KREATIF: Jurnal Pengabdian Masyarakat Nusantara, 2022)
Prostate cancer (Pca) is one type of cancer that attacks men. The risk factors for this cancer are age, genetics, lifestyle such as smoking, alcohol, a diet high in animal protein and low in fiber, genetics and vasectomy and occurs generally at the age of 50 years and over. Currently, the incidence of Pca has been found at the age of 40 years. This service activity is carried out to educate and increase the knowledge of the participants about PCa. The service activity was carried out in the hamlet of Mapung Buttu, Campalagian District and was attended by male farmers who were more than 40 years old. The dedication method uses lectures, which begins with a pre-test and daikhiri with a post-test. The results of the activity showed that there was an increase in the knowledge of the participants as seen from the ability to respond during the post test. Based on the results of the activity, it was concluded that this activity was very useful, as seen from the enthusiasm of the participants. This activity went smoothly because of the support and cooperation between the service team and the partner.